Analisis kemampuan forehand drive atlet tenis meja - Sari, Dessi Novita; Antoni, Despita (Edu Sportivo: Indonesian Journal of Physical Education, 2020)
The purpose of this study was to analyze the forehand drive ability of the Semen Padang table tennis athletes. This type of research is descriptive where the researcher only wants to see the actual situation in the field about the ability of forehand drive in playing table tennis. The population in this study were 18 beginner table tennis athletes in Semen Padang. The sampling technique used was proportional random sampling, so the number of samples was 15 people. To get data about the forehand drive capability, a test instrument was used with a target on the table. The analysis technique used is in accordance with the type of research, namely by using the percentage calculation. Based on the measurement and analysis, the results showed that the table tennis athlete of Semen Padang has the ability forehand drive in the medium category.